IMPACT COVID 19 PANDEMIC ON THE 4.0 SERVICE INDUSTRY (CASE STUDY ONLINE TRANSPORTATION GRAB IN KUPANG CITY) - Fransina W. Ballo; Maria Indriyani Hewe Tiwu; Desembry C. Nope (Universitas 17 Agustus 1945 Surabaya, 2022)
This explanatory study seeks to explain the impact of celebrity endorsement and reputation of the @OOTDFESS Forum as exogenous factors on customers' purchase intentions as endogenous variables. Using the questionnaire, the data was collected from 100 millennials aged 20 to 40 who are reside The Covid 19 pandemic had an impact on the world economy so that economic growth in countries has contracted. Indonesia did not escape the contraction of economic growth for 2 quarters. Indonesia has established large-scale social restriction policies to overcome the spread of Covid 19 for each of its regions, as well as Kupang City, East Nusa Tenggara. Almost economic sector was affected by the contraction in economic growth. This study aims to analyze the impact of the Covid pandemic on the service industry 4.0, especially Grab's online transportation service which operates in Kupang City. This study uses primary data by distributing questionnaires to 130 respondents of Grab car and Grab bike partners. The results of paired t tests of 130 respondents showed a significant difference in the demand and income variables before and during the Covid 19 pandemic. The consequences of the Covid 19 pandemic on demand for online grab transportation services have decreased and have an impact on reducing the income of grab car or grab bike partners. Keyword: Covid-19 Pandemic, 4.0 industry transportation, Grab